2009
DOI: 10.1645/ge-1898.1
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis of Eimeria spp. Populations in Relation to Performance Levels of Broiler Chicken Farms in Arkansas and North Carolina

Abstract: The impact of coccidiosis outbreaks on the productivity of broiler chicken farms can be substantial, depending on the severity of disease caused by particular species and strains of Eimeria. We examined the genetic diversity of Eimeria species present in commercial broiler farms in relation to their performance level. Four groups of broiler chicken farms in Arkansas (AR) and North Carolina (NC), having either high or low performance levels, were sampled for Eimeria spp. oocysts. We amplified gDNA from oocysts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 28 publications
4
47
0
1
Order By: Relevance
“…33). ITS sequences often are used for molecular diagnostics and phylogenetic analyses because of the sensitivity and specificity provided by their high copy number and relatively rapid evolution, although intraclonal polymorphism has proven limiting (33,34). Here, multiplex SNP genotyping for E. tenella provided far greater genetic power.…”
Section: Discussionmentioning
confidence: 99%
“…33). ITS sequences often are used for molecular diagnostics and phylogenetic analyses because of the sensitivity and specificity provided by their high copy number and relatively rapid evolution, although intraclonal polymorphism has proven limiting (33,34). Here, multiplex SNP genotyping for E. tenella provided far greater genetic power.…”
Section: Discussionmentioning
confidence: 99%
“…These assays have been utilised in commercial poultry flocks (Ogedengbe et al 2011), where it is relatively cost effective because tests for seven species of Eimeria can be carried out as a single PCR reaction. Schwarz et al (2009) examined the relationship between the genetic diversity of Eimeria infection with flock performance (measured as cost-per-mass produced), and found that more pathogenic species were associated with lower performance farms. DNA barcoding of some parasitic taxa has been problematic; for example, high nucleotide diversity in the COI region of platyhelminths made it difficult to design primers to amplify the entire phylum (Moszczynska et al 2009).…”
Section: Identification Of Agricultural Parasitesmentioning
confidence: 99%
“…Several techniques based on the polymerase chain reaction using primers that specifically targeting different regions of the Eimeria genome have been described (6,7,20,22,25,30). For molecular detection of Eimeria species in chickens, the DNA sequence of the first and second internal transcribed spacers (ITS-1 and ITS-2) of the nuclear DNA, which separate the ribosomal genes, is used most frequently.…”
Section: Acervulina E Brunetti E Maxima E Mitis E Necatrix Ementioning
confidence: 99%